FOREIGN TRADE OF THE REPUBLIC OF MOLDOVA: DEVELOPMENTS, TRENDS, PROSPECTS - Diana BRAGOI (Economica)
European integration has positively influenced Moldova's trade, redirecting it towards the EU markets and boosting part of the economy towards modernization. Nevertheless, consistent economic policies, dynamic institutional support, and investment in the structural diversification of the economy are needed to make the most of the advantages. In this context, the purpose of this study is to analyse the prospects for trade development of the Republic of Moldova in relation to the process of accession to the European Union, with emphasis on the dynamics of trade and alignment of the economic framework to EU standards. The methodology applied in this paper combines documentary analysis of relevant international agreements and trade policies with descriptive statistical analysis of Moldova's foreign trade data for the period 2015-2023. The study uses official sources, such as the National Bureau of Statistics, Eurostat and the World Bank, and applies economic indicators, such as the Relevant Comparative Advantage Index (RCA), to assess the country's trade specialization and external competitiveness. This approach provides a comprehensive overview of the impact of European integration process on Moldova's trade performance.